Small enterprise development : policies and programmes - Neck, Philip A., ed. (ILO GenevaCH, 1987)
Reviews small enterprise (SE) development policies and programmes, as applied in countries with various socio-economic settings. Contains 16 chapters covering various aspects of SE development including, inter alia, promotion of SEs; policy issues including financial aspects; creating the right environment for SEs; the case for government intervention; training owners and managers of small firms; training for entrepreneurship; developing indigenous entrepreneurship; management and extension services for SEs; technology and SE development; world Bank assistance to SEs in developing countries and research for SE development.